Empowerment of Increasing Economic Resilience Post Covid-19 Janjang Wulung Village Community Through Creative Economic Village Planning - Wardhana, Alvian; Ramayuda, Muhammad; Muhammad, Faza Farhan; Nariswari, Acyuta Putri; Arifin, Salsa Dwi Cahya; Wicaksono, Garin Ardi; Dianafi, Dani Rizky; Psf, Muhammad Ivan Riyandhika Saad (UI Scholars Hub, 2023)
Janjang Wulung Village is one of seven villages located at a highland of 593.73 meters above sea level in Puspo District, Pasuruan Regency, East Java. Janjang Wulung Village has natural resource potential from coffee, apples, avocados, and forest products supported by the plantation area, reaching 280.1 and farmers of 1,072 people. The livestock sector is also one of the superior productions in Janjang Wulung Village, with each household having 3-6 dairy cattle with a population of 602 people who work as breeders. However, the condition of COVID-19 limiting social activities resulted in a 20% to 40% decrease in income. So, planning the development of Janjang Wulung Village as a creative economy village is necessary to create an economically resilient village. Four analyses are used, including problem trees, analysis of village and community resilience, and SWOT, followed by the analysis of project alternatives that are resulting projects. The project includes village physical resilience, such as road rehabilitation projects, clean water system development projects, procurement projects, Wi-Fi Corner, food diversification innovation projects, technology development projects, and modules and poster projects using technology to support the development of the creative economy.